The Effects of TDI on Selected Properties of Ester Epoxy Alkyd Varnish - Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology, 2020)
This article presents the effects of toluene diisocyanate (TDI) on electrical properties of ester epoxy alkyd varnish. Through testing on breakdown voltage, dielectric constant, block resistivity, Tang (T g ) dielectric loss, the electrical properties of varnish were investigated. When TDI amount increased from to 4 - 10 (w/100w of epoxy resin), the breakdown voltage increased from 21.78 to 65.69 KV/mm. With TDI of 8 - 10 w/w, the dielectric constant was the best, about 2.78 - 3.02. With TDI of 8 w/w, the block resistivity was 6.8.10 14 W.cm and T g dielectric loss was 0.0069. The article also presents the effect of TDI on solvent- and heat resistance of the varnish.